Strengthening the Classroom Environment to Support Early Childhood Learning Activities at TK PKK Maguwoharjo - Usman, A'zhami Alim; Usman, Usman; Azizah, Faras Puji (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
This research aims to strengthen the classroom environment to support early childhood learning activities by analyzing the factors of the classroom environment that do not support learning activities, as well as to identify and understand the factors that influence the early childhood learning environment at PKK Maguwoharjo Kindergarten. The research method used is qualitative, with a case study approach through direct observation and interviews with teachers and parents. The results show that several factors in the classroom environment do not support early childhood learning activities, including failures in classroom arrangement that interfere with children's focus and concentration, lack of relevant learning resources, lack of variety and diversity of learning materials, lack of social interaction and collaboration in learning activities, lack of individualized attention to children, and physical discomforts such as noise, uncomfortable temperatures, lack of natural lighting, and poor air quality.  This research provides practical recommendations that can be implemented to improve the quality of the learning environment, especially in the management of the classroom environment for early childhood at PKK Maguwoharjo Kindergarten.Keywords - Learning Activities, Early Childhood, Classroom Environmental Factors, Less Supportive Environment, Classroom Environment Management